2019
DOI: 10.1002/mds.27792
|View full text |Cite
|
Sign up to set email alerts
|

Motor function and the probability of prodromal Parkinson's disease in older adults

Abstract: Background Identification and characterization of Parkinson's disease (PD) in its prodromal stage is crucial. Objective The objective of this study was to investigate the association between motor function and the probability of prodromal PD in a community‐dwelling older population. Methods We used data from a population‐based cohort of older adults (HELIAD study). Subjective motor function was evaluated with a 12‐item motor symptoms questionnaire and objective motor function indirectly with a physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The subjective perception of functional deficits plays an important role for both sensory and motor symptoms in all disease stages of PD 19 . We have quantified patient‐reported PNP symptoms with the NSS and correlated it to motor and nonmotor symptom scores.…”
Section: Resultsmentioning
confidence: 99%
“…The subjective perception of functional deficits plays an important role for both sensory and motor symptoms in all disease stages of PD 19 . We have quantified patient‐reported PNP symptoms with the NSS and correlated it to motor and nonmotor symptom scores.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical evaluations, including neurological clinical examination, were made by certified neurologists or, in rare occasions, by senior residents in neurology. Trained neuropsychologists were responsible for the neuropsychological assessment 11‐13 . For each participant, demographic data (age, sex) were collected together with detailed information on their medical history and family history (first‐degree relatives) and use of medications and tobacco products.…”
Section: Methodsmentioning
confidence: 99%
“…Details on how we ascertained the risk and prodromal markers already included in the 2015 MDS pPD criteria can be found in previous publications on the HELIAD population 12,13,27 . Regarding the markers added in the 2019 MDS pPD criteria, several definitions were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have quantified the gait speed of individuals in their natural environment, and they and others have found that declines in walking speed predict cognitive impairment and dementia [66][67][68]. Similarly, reductions in daily physical activity are associated with an increased risk of Alzheimer's disease and potentially PD [69][70][71]. Multiple non-motor features, including autonomic function and sleep, can also be evaluated.…”
Section: Benefits Of Deep Clinical Phenotypingmentioning
confidence: 99%